Radiation-induced neuropathological changes in the oligodendrocyte lineage with relevant clinical manifestations and therapeutic strategies. (3rd October 2022) - Lee, Rui Xue; Tang, Feng Ru
Abstract: Purpose: With technological advancements in radiation therapy for tumors of the central nervous system (CNS), high doses of ionizing radiation can be delivered to the tumors with improved accuracy. Despite the reduction of ionizing radiation-induced toxicity to surrounding tissues of the CNS, a wide array of side effects still occurs, particularly late-delayed changes. These alterations, such as white matter damages and neurocognitive impairments, are often debilitative and untreatable, significantly affecting the quality of life of these patients, especially children. Oligodendrocytes, a major class of glial cells, have been identified to be one of the targets of radiation toxicity and are recognized be involved in late-delayed radiation-induced neuropathological changes. These cells are responsible for forming the myelin sheaths that surround and insulate axons within the CNS. Here, the effects of ionizing radiation on the oligodendrocyte lineage as well as the common clinical manifestations resulting from radiation-induced damage to oligodendrocytes will be discussed. Potential prophylactic and therapeutic strategies against radiation-induced oligodendrocyte damage will also be considered. Conclusion: Oligodendrocytes and oligodendrocyte progenitor cells (OPCs) are radiosensitive cells of the CNS. Here, general responses of these cells to radiation exposure have been outlined. However, several findings have not been consistent across various studies. For instance, cognitive decline in irradiated animals was observed to be accompanied by obvious demyelination or white matter changes in several studies but not in others. Hence, further studies have to be conducted to elucidate the level of contribution of the oligodendrocyte lineage to the development of late-delayed effects of radiation exposure, as well as to classify the dose and brain region-specific responses of the oligodendrocyte lineage to radiation. Several potential therapeutic approaches against late-delayed changes have been discussed, such as the transplantation of OPCs into irradiated regions and implementation of exercise. Many of these approaches show promising results. Further elucidation of the mechanisms involved in radiation-induced death of oligodendrocytes and OPCs would certainly aid in the development of novel protective and therapeutic strategies against the late-delayed effects of radiation.